2011
DOI: 10.3892/ol.2011.315
|View full text |Cite
|
Sign up to set email alerts
|

CD38 expression as response of hematopoietic system to cancer

Abstract: Abstract. Erythrocyte and lymphocyte NAD + glycohydrolase levels were previously found to be elevated in cancer patients. These results were confirmed in an animal model. The administration of live Ehrlich ascites tumor cells to BALB/c mice led to increases in erythrocyte and lymphocyte NAD + glycohydrolase, along with tumor development. Serum samples, ascites fluid from mice with developed tumors, serum samples from cancer patients and Ehrlich cell supernatants had a similar stimulatory effect when administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Perenkov et al (35) found that the expression of the CD38 gene is heterogeneous in the tumor cells of patients with colorectal cancer. CD38 expression is triggered at least in part by a certain cytokine(s) secreted by cancer cells (36). our data are consistent with those observations and suggest that CD38 maybe play an important role in cervical cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Perenkov et al (35) found that the expression of the CD38 gene is heterogeneous in the tumor cells of patients with colorectal cancer. CD38 expression is triggered at least in part by a certain cytokine(s) secreted by cancer cells (36). our data are consistent with those observations and suggest that CD38 maybe play an important role in cervical cancer.…”
Section: Discussionsupporting
confidence: 92%